Update on the First Finding of the Rat Lungworm, Angiostrongylus cantonensis, in Rattus spp. in Continental Europe, Valencia, Spain, 2022 - María Teresa Galán-Puchades; Mercedes Gómez-Samblás; Antonio Osuna; Sandra Sáez-Durán; Rubén Bueno-Marí; Màrius V. Fuentes (Pathogens, 2023)
The rat lungworm, Angiostrongylus cantonensis, is an emerging parasite that can cause eosinophilic meningitis in humans. Over the past 60 years, the worm has greatly expanded its original Asian distribution to most tropical and subtropical areas of the world, mostly by traveling on ships with its definitive hosts, rats. Angiostrongylus cantonensis was recently found for the first time in Continental Europe, specifically in 3 (2 Rattus norvegicus and 1 Rattus rattus) out of 27 rats trapped in the sewer system of the city of Valencia, Spain. Updating the investigation, the parasite has subsequently been found in 8 (5 R. norvegicus and 3 R. rattus) out of 94 rats analyzed. The highest prevalence of infection (20%) was obtained in rats trapped in the orchards that surround the city, where both snails and slugs (intermediate hosts) abound, and where vegetables consumed in Valencia, other parts of Spain, and abroad, are produced. The presence of the parasite in rats does not necessarily mean that the disease it causes becomes a relevant public health concern since it strongly depends on the food habits of the population at risk. If proper precautions are taken, the risk of acquiring neuroangiostrongylosis should be minimal.